(untitled) (Scientific journal of the Fergana State University, 2024)
The article is based on the improvement of scientific and methodological foundations and coordination of management mechanisms in the field of emergency risk management. Due to the unique geographical location of the Republic of Uzbekistan, serious geological and climatic threats, which can cause many natural disasters, and the problems of global climate change, the problems of permanent negative impact on the population and economy of the republic have been revealed.